A method for approximating the CHF of subcooled flow boiling in microgravity by ground tests. (January 2020) - Liu, Bin; Yuan, Bo; Xu, Pengzhuo; Zhao, Jianfu; Zhang, Yonghai; Wei, Jinjia; Yang, Yang; Cao, Qian
Research highlights: A method to find the subcooled flow boiling CHF in microgravity by ground tests was proposed. The method was validated by drop tower experiments. The method has the advantages of convenience, economy and precision. Abstract: A method for approximating the critical heat flux (CHF) of subcooled flow boiling in microgravity by ground tests was proposed. The method suggests that the flow boiling CHF in microgravity is less than that in normal gravity at a heating surface orientation ( φ ) of 135° but is greater than that in normal gravity when φ =  315° at the corresponding conditions. The method was validated by drop tower experiments, and good agreement was observed from the results of all five tested cases. The method provided a new way to find the CHF of subcooled flow boiling in microgravity by ground tests. Graphical abstract: Image, graphical abstract